PERAN PEMBIMBING KLINIK TERHADAP KEPUASAN MAHASISWA PADA PENGALAMAN PRAKTEK KLINIK LAPANGAN PERTAMA - Dermawani Damanik; Julwansa Saragih; Julianto (Universitas Prima Indonesia, 2021)
Clinical supervisors’ play a vital role in the student learning process in carrying out direct action on patients in the hospital, affecting competence in cognitive, attitudes, and psychomotor students in providing nursing care and developing professional organizations. The study aimed to identify the clinical supervisors’ role and student satisfaction in the first field clinical practice RS Tentara TK IV 010701 Pematangsiantar. The sampling technique was a saturated sampling technique with as many as 75 respondents. The study was conducted from February to March 2020. The instruments in this study used a questionnaire. Student satisfaction data were collected using a nursing student satisfaction assessment questionnaire in the first clinical practice modified by Nejad et al. Statistical test is using Rho spearmen. The results showed that the majority of respondents were between 17-21 years of age, as many as 65 people (86.7%), the majority of whom were 56 women (74.7%), the role of clinical supervisors the majority were in the good category as many as 62 respondents (82.7%), student satisfaction in the first field clinical practice the majority were in the high category, 65 respondents (86.7%), the analysis with the SPSS program obtained a statistical value of p <0.05, namely of 0.000, which means that there is a significant correlation, meaning that there is a positive effect between clinical supervisors’ role and student satisfaction in the first field clinical practice. It is recommended that the hospital management and education keep making improvements and motivating clinical supervisors to carry out their roles seriously the responsibilities that have been given.